Finite element analysis of composite cone under compression test - Ahmad Faiz, Fauzee (2009)
A study of finite element analysis of composite cone under compression test is presented in this thesis. The behaviors of different angles of composite cone under compression test were been analyzed. The study and analyzed performance of composite cone in energy absorption point of view also had been carried out. The analysis were conducted using finite element Algor software and the theoretical value were calculated based on theoretical determination of properties on lamina level. It has been observes that with increasing cone angle from 5⁰ to 15⁰ for all cone, composite cone can withstand higher load and the specific absorption was improved. It also concluded here, the 15⁰ cone stand highest load and energy absorption.